2019
DOI: 10.3233/wor-182838
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of subjective perceived rating for grip strength depending on handedness for various target force levels

Abstract: BACKGROUND: Measurement of hand exertion is very important to quantify the risk of Work-related Musculoskeletal Disorders (WMSDs) in manufacturing fields. Although a direct measurement is the most accurate way to quantify physical load, it is expensive and time consuming. To solve this limitation, a subjective self-report method has been proposed as a possible alternative. OBJECTIVE: The purpose of this study was to analyze the accuracy of subjective perception for grip force exertions associated with handedne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Studies have identified significant overlap between the anterior bundle of the UCL and flexor digitorum superficialis (FDS) tendon insertion (45.6%; 95% CI: 38.1-53.6), and demonstrated that muscle activation of the finger flexors reduced humeroulnar joint gap under valgus stress 25,27 . A study by Kong et al 28 found variability in self-perceived percentages of maximum voluntary grip strength based on hand dominance; rates of contraction in the dominant hand were routinely underestimated, while rates of contraction in the non-dominant hand were routinely over-estimated. These findings may indicate a more nuanced role of FDS in providing valgus stability.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified significant overlap between the anterior bundle of the UCL and flexor digitorum superficialis (FDS) tendon insertion (45.6%; 95% CI: 38.1-53.6), and demonstrated that muscle activation of the finger flexors reduced humeroulnar joint gap under valgus stress 25,27 . A study by Kong et al 28 found variability in self-perceived percentages of maximum voluntary grip strength based on hand dominance; rates of contraction in the dominant hand were routinely underestimated, while rates of contraction in the non-dominant hand were routinely over-estimated. These findings may indicate a more nuanced role of FDS in providing valgus stability.…”
Section: Discussionmentioning
confidence: 99%
“…However, research directly investigating how perceived effort aligns with the targeted objective performance relative to maximum capacity has led to mixed results 32,33 , suggesting a nonlinear alignment pattern. This indicates that changes in the perceived effort do not map onto respective changes in objective performance in a way that is directly equivalent 32,34 .…”
Section: Alignment Of Subjectively Perceived Effort and Objective Beh...mentioning
confidence: 98%
“…Previous studies that evaluated perceived ratings of grip strength indicated a nonlinear relationship between the perceived and actual force of exertion [11]. Pinchvero et al [17,18] also reported a nonlinear relationship between the perceived and actual force of exertion.…”
Section: Introductionmentioning
confidence: 93%
“…Park and Yun [10] also estimated grip force exertion using the Borg's CR-10 scale and found that the correlation between the measured force and the perceived exertion ranged from 0.8 to 0.99. Kong et al [11] and Prasad and Manivannan [12] reported that the perception of handgrip force differed according to the handedness. Therefore, while substantial research has already been conducted on grip strength, very few studies investigated thumb force exertion levels and self-reporting estimates, even though the thumb plays a major role in various manual tasks [13][14][15].…”
Section: Introductionmentioning
confidence: 99%